RSSI measurements of a GSM signal within an indoor environment - Ismail, Ahmad Fadzil; Jakpar, Muhamad Jamil; Za’bah, Nor Farahidah; Badron, Khairayu; Hashim, Wahidah (Science & Engineering Research Support Society, 2017)
Studies has suggested that the association between Received Signal Strength Indication (RSSI) and measured distance between the transmitter and receiver can be one of the key elements for ranging and localization technologies. In this study, measurements of RSSI and the distance between 1800MHz receiver and transmitter within an indoor environment were acquired, recorded and analyzed. Using the data, correlation for a select indoor environment was derived. By comparing the recorded distance values acquired at set RSSI with values calculated based on the Free Space Path Loss equation, provisional estimation of the indoor signal fading can be established. The experiment was the initial part of a three-stage work that will later entail the comparison to that of outdoor as well as clean room environments. The final result of the study hopes to achieve a simple yet improved indoor fading model experienced by mobile communication signals.